Menyoal Landasan Hukum Konsep Kafaah: Pembacaan Ulang Atas Ayat-Ayat Kafaah Perspektif Wahbah al-Zuhayliy - Ach. Mahbub, Mahbub; Muh. Fathoni Hasyim, Fathoni (Mahad Aly Al Fithrah, 2022)
One of the diversity of the interpretation results of a Qur’anic verses is the concept of kafaah in marriage. The verses about the concept of kafaah that are used as the basis of the law by most classical Jurisprudence groups are appertain explicit. Therefore, the concept of kafaah has become one of the problems debate among Jurisprudence since long time ago until now. Of course, this concept of kafaah will be very interesting if it is understood through the approach of qur'an and Tafsir science. This article seeks to re-read the meaning of the verses that are used as arguments for the concept of kafaah in marriage through the approach of Wahbah al-Zuhayli>ythought.The writing of this article is a qualitative research, namely research that makes library materials the main source (data). In data collection techniques, this article uses the thematic model technique “mawdu>‘i” with a focus on the verses on which the concept of kafaah is based.In this article, revealed that there are verses that alleged to be the basis for the concept of classical Jurisprudence. That seven verses are not all properly said to be the basis of the kafaah law. According to the author, there are three verses that properly used as the basis of kafaah, even from the aspect of al-di>nin the sense of al-diyanah, which means al-taqwa or al-salah can also be called praiseworthy morals (spiritual morals): First, surah al-Nu>r [24]: 3. Second, surah al-al-Nu>r [24]: 26. and Third, one verse as a support or reinforcement of the legal basis of kafaah from the aspect of al-di>nnamely surah al-Sajadah [32]: 18.